Saluran dan margin pemasaran budidaya Ikan Mas (Cyprinus carpio L) di Desa Nanggala Kabupaten Toraja Utara - Saputri Rasi Emben, Afni; Yusuf, Sarini; Ruslaini; Annaastasia, Nurhuda; Sriwulan, Desy (Universitas Halu Oleo, 2023)
This study aims to determine and analyze the marketing channel and marThis study aims to determine and analyze the marketing channel and marketing margin of carp (Cyprinus carpio L) cultivation in Nanggala Village, North Toraja Regency. The method of determining the location was performed intentionally or purposively. The informant determination technique in this study used cluster random sampling. The data collection was consisted of primary data and secondary data, and the data analysis method used qualitative descriptive methods to explain marketing channel patterns, while the marketing margin was counted by subtracting the price of fish at the consumer level with the price at the producer level. The results showed that the marketing channel of carp in Nanggala Village was consisted of three marketing channels, namely: marketing channel I, the farmer sailed directly their product to consumer; marketing channel II, namely: the farmer sailed their carp fish to collector and the collector sailed the carp fish the to consumer; and marketing channel III, namely: the farmer to collector to the retailer and then to the consumer. The marketing margin of common carp in marketing channel II was IDR 10.000/kg and marketing channel III was IDR 5.000/kg. The existing marketing channel in Nanggala Village was categorized in the efficient categoryketing margin of carp (Cyprinus carpio L) cultivation in Nanggala Village, North Toraja Regency. The method of determining the location was performed intentionally or purposively. The informant determination technique in this study used cluster random sampling. The data collection was consisted of primary data and secondary data, and the data analysis method used qualitative descriptive methods to explain marketing channel patterns, while the marketing margin was counted by subtracting the price of fish at the consumer level with the price at the producer level. The results showed that the marketing channel of carp in Nanggala Village was consisted of three marketing channels, namely: marketing channel I, the farmer sailed directly their product to consumer; marketing channel II, namely: the farmer sailed their carp fish to collector and the collector sailed the carp fish the to consumer; and marketing channel III, namely: the farmer to collector to the retailer and then to the consumer. The marketing margin of common carp in marketing channel II was IDR 10.000/kg and marketing channel III was IDR 5.000/kg. The existing marketing channel in Nanggala Village was categorized in the efficient category.